Sorry, I Can't Open My Camera! Social Anxiety Levels of Prospective Teachers In E-Learning Environments During Covid-19 Pandemic - Görkem Avcı; Erkan Dinc; Servet Üztemur (International Journal of Contemporary Educational Research, 2023)
The present study aims to determine the social anxiety levels of prospective teachers in e-learning environments. The research adopts the cross-sectional survey model. The study group consists of 506 pre-service teachers through a convenience sampling technique from a state university in northern Turkey during the fall semester of the 2021-2022 academic year. The data are collected online through the “Social Anxiety Scale for E-Learning Environments” in the spring semester of the 2021-2022 academic year. The study found that teacher candidates have a moderate level of social anxiety in e-learning environments which unfavorably affects academic achievement. Moreover, it is concluded that gender is not directly affecting social anxiety in e-learning environments, but the grade level is influential on social anxiety. There is a positive correlation between prospective teachers’ self-efficacy in using computers and their social anxiety levels in e-learning environments. This study has revealed new empirical results on the reflections of social anxiety in e-learning environments. The results are discussed in line with the relevant literature and some recommendations are made.